Experimental study of the strength of straw rope as a material for making mattresses - Agus Wijianto; Ma'a, Mustaza; M Ghifari Hadi; Roni Novison (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
This experimental study thoroughly investigates the impact of soaking straw ropes using three different liquids oil, urea, and salt, on tensile strength and other mechanical properties. The experiment involved meticulously prepared straw rope samples, each with standardized diameter and length, subjected to rigorous testing using a tensile testing machine to gather precise and reliable data. The empirical results revealed significant differences in tensile strength, strain, and elastic modulus among the samples, largely influenced by the type of soaking liquid used during the testing phase. Straw ropes immersed in oil exhibited the highest tensile strength and strain before fracture, followed closely by ropes soaked in urea and salt, while ropes treated with starch showed the least enhancement in mechanical properties. This comprehensive examination provides profound insight into the behavior and characteristics of straw ropes when exposed to various soaking liquids, highlighting the potential modifications in their mechanical performance. The findings contribute valuable knowledge for practical applications in industries such as construction, agriculture, and other sectors where straw ropes are employed as a material requiring specific mechanical attributes. Moreover, this research underscores the importance of selecting appropriate soaking liquids to enhance the mechanical properties of straw ropes, offering a foundation for future studies and practical implementations aimed at optimizing the use of straw ropes in various applications. By elucidating the effects of different soaking treatments, this study not only advances the understanding of straw rope mechanics but also presents actionable information to improve material performance in real-world scenarios.